Behaviour of lockbolts in slip‐resistant connections for steel structures. Issue 4 (7th November 2017) - Ebert, Andreas; Dörre, Maik; Glienke, Ralf
Abstract: HV bolts are often used for safe and durable connections in steel structures. However, this well‐known and established bolting system has some disadvantages. Those include the scattering of the initial preload by the torque‐controlled tightening method and the risk of self‐loosening during fatigue loads due to lateral displacement of the components in connections with high loads. In this respect, the lockbolt technology has some advantages regarding the initial preload and loss of preload; both will be discussed in detail in this paper. The technology was invented in the 1940s and is mainly used in automotive, aviation, truck, trailer, rail, bus, agriculture, mining and military applications. Its use in structural steelwork, and especially for slip‐resistant connections, has been mainly made possible through individual experimental investigations by users of the technology. Some applications call for its use in slip‐resistant connections according to EN 1090‐2 and Eurocode 3, e.g. the wind industry for new tower concepts with higher hub heights, and steel girder bridges. These connections can be subjected to fatigue and/or significant load reversal. The load‐bearing capacity (or slip resistance) of a slip‐resistant connection is mainly determined by the level of preload in the bolt and the coating system applied to the faying surfaces. However, the preload is determined by the type of bolt, and lockbolts can be used as an alternative bolting system. This paper describes a comparative study of HV bolts and lockbolts regarding their use in slip‐resistant connections for steel structures. The design and execution of lockbolts will be presented. Investigations will be presented which compare HV bolts and lockbolts regarding the assembly preload, the slip resistance by performing slip load tests and the long‐term behaviour with respect to loss of preload for maintenance‐free connections. Furthermore, there is a discussion of the results of an online monitoring system for measuring the preload in HV bolts and Bobtail lockbolts in an alternative tower for wind turbines with the use of slip‐resistant connections.